Combining a New Exome Capture Panel With an Effective varBScore Algorithm Accelerates BSA-Based Gene Cloning in Wheat - Dong, Chunhao; Zhang, Lichao; Chen, Zhongxu; Xia, Chuan; Gu, Yongqiang; Wang, Jirui; Li, Danping; Xie, Zhencheng; Zhang, Qiang; Zhang, Xueying; Gui, Lixuan; Liu, Xu; et al. (Frontiers in Plant Science, 2020)
The discovery of functional genes underlying agronomic traits is of great importance for wheat improvement. Here we designed a new wheat exome capture probe panel based on IWGSC RefSeq v1.0 genome sequence information and developed an effective algorithm varBScore that can sufficiently reduce the background noise in gene mapping and identification. An effective method, termed bulked segregant exome capture sequencing (BSE-Seq) for identifying causal mutations or candidate genes was established by combining the use of new designed wheat exome capture panel, sequencing of bulked segregant pools from segregating populations, and the robust algorithm varBScore. We evaluated the effectiveness of varBScore algorithm on SNP call using the published dataset for mapping and cloning the yellow rust resistance gene Yr7 in wheat. Furthermore, using BSE-Seq, we rapidly identified a wheat yellow leaf mutant gene ygl1 in an ethyl methanesulfonate (EMS) mutant population and found that a single mutation of G to A at 921 position in the wild type YGL1 gene encoding magnesium-chelatase subunit chlI caused the leaf yellowing phenotype. We further showed that mutation of YGL1 through CRISPR/Cas9 gene editing led to a yellow phenotype on the leaves of transgenic wheat, indicating that ygl1 is the correct causal gene responsible for the mutant phenotype. In summary, our approach is highly efficient for discovering the causal mutation or gene cloning in wheat.